Effects of Guanxinshutong Capsules as Complementary Treatment in Patients With Chronic Heart Failure: Study Protocol for a Randomized Controlled Trial - Wang, Yu; Xu, Jiaping; Yang, Jiehong; Zhang, Ling; Pan, Yuanjiang; Dou, Liping; Zhou, Peng; Xu, Yizhou; Li, Chang; He, Yu; Zhou, Huifen; Yu, Li; et al. (Frontiers in Pharmacology, 2021)
Chronic heart failure (CHF) is a common cardiovascular disease with high mortality and a poor prognosis, which places heavy burdens upon society and families. Traditional Chinese medicine (TCM) has been used extensively as complementary treatment for CHF. Guanxinshutong (GXST) capsules are used commonly for the treatment of coronary heart disease (CHD). Experimental research and small-sample clinical trials have shown that GXST can attenuate CHF. However, the effects of GXST as complementary medicine in CHF treatment lack high-quality clinical evidence. We have designed a multicenter, randomized, double-blind, placebo-controlled clinical trial that explores the efficacy and safety of using GXST compared with placebo for patients with CHF with reduced left ventricular ejection fraction (LVEF). A total of 480 participants will be assigned randomly to the GXST group or placebo group at a 2:1 ratio. GXST and placebo will be added to standard treatment for 12 weeks, and then followed up for another 40 weeks. The primary outcome is the improvement value of 6-min walk distance, and the secondary outcomes include plasma levels of N-terminal pro-B-type natriuretic peptide, New York Heart Association classification, Minnesota Living with Heart Failure Questionnaire scores, echocardiographic parameters, and clinical endpoint events. Adverse events will be monitored throughout the trial. Data will be analyzed following a predefined statistical analysis plan. This study will show the effects of the specific use of GXST in CHF patients with reduced LVEF. The Research Ethics Committee of the Second Affiliated Hospital of Zhejiang Chinese Medical University has approved this study (2019-Y-003-02). Written informed consent of patients will be required. This trial is registered in the Chinese Clinical Trial Registry (ChiCTR1900023877). Our results will be disseminated to the public through peer-reviewed journals, academic conferences, and the Internet.